2011
DOI: 10.2106/jbjs.k.00108
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Diversity in Orthopaedic Surgery Residency Programs

Abstract: Minority representation in orthopaedic residency programs has increased over time for Asians, Hispanics, and African-Americans. In spite of these gains, orthopaedic surgery has remained the least diverse of the specialty training programs considered in this study. While further efforts are needed to determine the factors underlying this lack of representation, we suggest a series of interventions that can be expected to enhance diversity in orthopaedic residencies as well as in the profession as a whole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 29 publications
7
97
0
1
Order By: Relevance
“…The prolonged hours of surgical training appear less daunting when they are limited by work-hour regulations, and this might account for the increased pursuit of surgical residencies by women [1]. The fact that women choose orthopaedics for occupation-related and intellectual reasons correlates well with the finding in a study of 90 residents that women and men in residency performed similarly by objective and subjective measures [15]. Women reported higher satisfaction with career choice than their male colleagues [18].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The prolonged hours of surgical training appear less daunting when they are limited by work-hour regulations, and this might account for the increased pursuit of surgical residencies by women [1]. The fact that women choose orthopaedics for occupation-related and intellectual reasons correlates well with the finding in a study of 90 residents that women and men in residency performed similarly by objective and subjective measures [15]. Women reported higher satisfaction with career choice than their male colleagues [18].…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies have suggested that a bias against surgical specialties overall may play a role in women's interest in orthopaedics [4]. Additionally, orthopaedic surgical programs with a stated commitment to diversity have shown higher percentages of women and underrepresented minorities [15,21]. Finally, lack of mentorship and women faculty in training programs have been cited as potential causes of smaller numbers of women medical students pursuing this specialty [22].…”
Section: Introductionmentioning
confidence: 99%
“…On average, during the period of study, African American, Hispanic/Latino, and American Indian/Alaska Native applicants applied to fewer programs each year than the national average (45.3, 46.9, and 49.5, respectively, versus 50.4). Native Hawaiian/other Pacific Islander applicants averaged more applications per year than e96 (4) the national average over the period of study (57.5 versus 50.4); however, there were no more than 4 applicants in this category per year, so the average number of applications may be skewed by a single outlier.…”
Section: Resultsmentioning
confidence: 85%
“…For the entire group, regardless of age, mentorship was surprisingly less influential in choice of specialty for AAaAD otolaryngologists. Although other specialities demonstrate that increased numbers of minorities and mentorship have impact on recruitment to the specialty, [9][10][11] similarly notable for women, [12][13][14][15][16] it is plausible that otolaryngology has proportionally fewer mentors in position of influence and impact for AAaAD medical students than other specialities such as general surgery, urology, orthopedics, and obstetrics and gynecology. With only two respondents mentored by an AAaAD otolaryngologist, our study shows a gap in the trends observed in general surgery, where Powers et al found that AAaAD surgical residents are more likely to pursue a career in academic medicine if they had AAaAD mentors.…”
Section: Discussionmentioning
confidence: 99%